A Double-Blind, Randomized Trial of High-Dose vs Standard-Dose Influenza Vaccine in Adult Solid-Organ Transplant Recipients. (14th December 2017) - Natori, Yoichiro; Shiotsuka, Mika; Slomovic, Jaclyn; Hoschler, Katja; Ferreira, Victor; Ashton, Peter; Rotstein, Coleman; Lilly, Les; Schiff, Jeffrey; Singer, Lianne; Humar, Atul; Kumar, Deepali
Abstract: Background: The annual standard-dose (SD) influenza vaccine has suboptimal immunogenicity in solid organ transplant recipients (SOTRs). Influenza vaccine that contains higher doses of antigens may lead to greater immunogenicity in this population. Methods: We conducted a randomized, double-blind trial to compare the safety and immunogenicity of the 2016–2017 high-dose (HD; FluzoneHD, Sanofi) vs SD (Fluviral, GSK) influenza vaccine in adult SOTRs. Preimmunization and 4-week postimmunization sera underwent strain-specific hemagglutination inhibition assay. Results: We enrolled 172 patients who received study vaccine, and 161 (84 HD; 77 SD) were eligible for analysis. Seroconversion to at least 1 of 3 vaccine antigens was present in 78.6% vs 55.8% in HD vs SD vaccine groups ( P < .001), respectively. Seroconversions to A/ H1N1, A/H3N2, and B strains were 40.5% vs 20.5%, 57.1% vs 32.5%, and 58.3% vs 41.6% in HD vs SD vaccine groups ( P = .006, P = .002, P = .028, respectively). Post-immunization geometric mean titers of A/H1N1, A/H3N2, and B strains were significantly higher in the HD group ( P = .007, P = .002, P = .033). Independent factors associated with seroconversion to at least 1 vaccine strain were the use of HD vaccine (odds ratio [OR], 3.23; 95% confidence interval [CI], 1.56–6.67) and use of mycophenolate doses <2 g daily (OR, 2.76; 95% CI, 1.12–6.76). Conclusions: HD vaccine demonstrated significantly better immunogenicity than SD vaccine in adult transplant recipients and may be the preferred influenza vaccine for this population. Clinical Trials Registration: NCT03139565. Abstract : This randomized trial demonstrates superior immunogenicity of high-dose influenza vaccine compared to standard-dose trivalent vaccine in immunosuppressed organ transplant recipients. High doses of mycophenolate were associated with reduced immunogenicity.